Investigation of the work of the road construction at the sites by pipe drenes from materials of different origin - Slavinska, Оlena; Savenko, Vyacheslav; Bubela, Andrey; Yaremov, Andrey (Eastern-European Journal of Enterprise Technologies, 2018)
The paper reports research into operation of road structures with tubular drains made from materials with different physical-mechanical properties, which makes it possible to identify basic factors that affect operational conditions under the influence of own mass and the rated load from rolling stock in accordance with the building norms of Ukraine. Non-standard road structures were simulated in the SCAD environment. The results of numerical simulation allowed us to derive diagrams of normal stresses and deformations of structural layers in road surfacing, as well as in the body of tubular drains. The calculations were performed both for the standard and the actual compaction of material used as a trench backfill, for a PVC pipe and a concrete pipe. Consideration of tubular openings in solid layered road structures made it possible to estimate the actual stressed-deformed state at the sections of roads that require control over a water-heat mode. The proposed method of study enables the selection of individual design-structural parameters for drainages of shallow laying for general-purpose public roads of different technical categories as opposed to the standard approaches implied by the building regulations of Ukraine.